Molecular effects on ion-electron emission from clean metal surfaces. - Baragiola, R. A.; Alonso, E. V.; Auciello, O. R.; Ferrón, J.; Lantschner, G. R.; Oliva Florio, A. (American Chemical Society, 1978)
Fil: Baragiola, R. A. Comisión Nacional de Energía Atómica; Argentina